2018
DOI: 10.1037/adb0000394
|View full text |Cite
|
Sign up to set email alerts
|

Examining the pathways between bully victimization, depression, academic achievement, and problematic drinking in adolescence.

Abstract: In this article, we expand and test several theoretical models addressing the longitudinal relationships between bully victimization, depression, academic achievement, and problematic drinking from 3 approaches: Interpersonal risk model, symptom driven model, and a transactional model. Unfortunately, prior research has failed to consider these associations at the within-person level, which is arguably a more relevant level of analysis. Participants were 1,875 students sampled from four Midwestern middle school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 76 publications
4
44
0
1
Order By: Relevance
“…Findings from the current study also support the academic achievement risk pathway proposed by the socio-ecological framework (Hong et al, 2014), such that declines in grades accounted for how peer victimization conferred risk for substance use. The academic achievement difficulty pathway was relevant for both girls and boys, but may be gender-specific with regard to the form of peer victimization and type of substance, which extends the only prior examination of this pathway that focused on binge drinking (Davis et al, 2018). Among girls, more frequent social media victimization predicted greater decreases in grades, which in turn increased risk for vaping.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Findings from the current study also support the academic achievement risk pathway proposed by the socio-ecological framework (Hong et al, 2014), such that declines in grades accounted for how peer victimization conferred risk for substance use. The academic achievement difficulty pathway was relevant for both girls and boys, but may be gender-specific with regard to the form of peer victimization and type of substance, which extends the only prior examination of this pathway that focused on binge drinking (Davis et al, 2018). Among girls, more frequent social media victimization predicted greater decreases in grades, which in turn increased risk for vaping.…”
Section: Discussionmentioning
confidence: 69%
“…These hypotheses are consistent with affect-regulation and self-medication models of substance use, which posit that individuals engage in substance use to alleviate emotional distress (Sher & Slutske, 2003; Tomlinson & Brown, 2012). Longitudinal studies consistently support this meditational pathway in adolescents (Davis et al, 2018; Earnshaw et al, 2017; Zapolski et al, 2018). Yet, the relevance of the depressive symptoms risk pathway for different forms of peer victimization and specific substances remains unclear, as no known studies have differentiated between overt, relational, and social media victimization.…”
Section: Pathways From Peer Victimization To Substance Usementioning
confidence: 82%
“…20 Previous studies have shown that students with lower levels of academic competence are more likely to display conduct problems such as aggression, bullying, and substance abuse. [29][30][31][32] Therefore, individuals with poor academic achievement may use bullying to gain self-worth.…”
Section: Relationship Between Academic Achievement and Bullyingmentioning
confidence: 99%
“…2019 El consumo de alcohol tiene una importante repercusión a nivel de salud general, ya que se asocia a problemas psiquiátricos y médicos (Molina y Nelson, 2018). Los malos resultados académicos entre universitarios se han relacionado con la ingesta excesiva de alcohol (Davis et al, 2018), y, más concretamente algunos autores apuntan al consumo de tipo atracón o BD (Patte, Quian y Leatherdale, 2017). Además, el uso continuado del consumo de alcohol entre los jóvenes universitarios se relaciona directamente con absentismo escolar y conductas delictivas (Flaherty, Sutphen y Ely, 2012).…”
Section: Introductionunclassified